Analysis of Kicking Technique Skills of Extracurricular Pencak Silat SMP Negeri 7 Muaro Jambi - Randi Wahyu Oktareza; Anggrawan Janur Putra (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2025)
The purpose of this study is to determine the condition of basic pencak silat kicking skills in extracurricular students of SMP Negeri 7 Muara Jambi. The method used is a quantitative method with a descriptive research form. The population in this study were all extracurricular pencak silat students of SMP Negeri 7 Muara Jambi totaling 8 students so this study used the total sampling method. The test instrument consisted of 17 items consisting of straight kicks, crescent kicks, T kicks, and back kicks, where each skill will be tested starting from the stance, leg lift, whip and pull. During the study, the researcher was accompanied by a competent partner. The results of the study obtained were 2 students in the